IMPRESSIONABILITY OF INDIAN ADOLESCENTS: A CHALLENGING ROAD AHEAD - Dr.V. RAMYA 1, Dr. K. SHOBA 2, Dr. G. RAMESH 3 (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
Adolescents are impressed with things not experienced in childhood and derive pleasure in luring new things. If what is needed to youth is not readily available to them, they are easily carried away by personalities who are doing gimmicks on television sets, cinema and social media. Advertisements in TV and social media are easily attracting the present day adults towards the things which they not only need but are not capable of buying out of honestly earned income. What is seen and heard is easily creating a long- lasting impression in the minds of individuals. Without identifying the difficulties, the celebrities had to undergo to become famous and what they are today, youngsters try to emulate them getting into the glimpse the things watched. When one is not able to pay the price for short-cut success, he /she either ends the life or put into serious depression. Unwarranted impressions among the youth will do more damage to the lives of adults in India than anything constructive for societal transformation. Parents and teachers have huge role in shaping the attitude of their wards especially in their adolescent period. The present study is an attempt to diagnose the reasons of impressionability of youngsters in India, divulge the causes and impact of such impression and offer some suggestions to overcome such a phenomenon.